ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF STAPHYLOCOCCUS AUREUS ON CLINICAL ISOLATES AND EFFICACY OF LABORATORY TESTS TO DIAGNOSE MRSA: A MULTI-CENTRE STUDY - Bukhari, Syed Zahid; Ahmed, Safia; Zia, Naheed (Journal of Ayub Medical College Abbottabad, 2011)
Background: The global problem of increasing trend in antimicrobial resistance is particularly pressing in the developing countries, where the Methicillin-Resistant Staphylococcus aureus (MRSA) is often the severe casual agent in hospital-acquired infections. Methods: This multi-centre surveillance prospective study was planned to define the magnitude of problem of MRSA among clinical isolates from four teaching hospitals of Lahore Pakistan; Mayo, Services, Jinnah and Shaikh Zayed Hospitals during April 2006-March 2008. Identification of organisms was done by the standard Microbiology methods. MRSA isolates identified on Kirby-Bauer disc diffusion were further evaluated by minimum inhibitory concentration on BD PhoenixTM system and detection of mecA gene by pulsed-field gel electrophoresis (PFGE) PCR. Results: Of the total 1,102 S. aureus isolates, oxacillin resistance was found in 462 on disc diffusion and 420 on MIC while mecA gene was detected from 307 strains. The prevalence of MRSA among S. aureus isolates was 41.9%, 38.1% and 27.9% on disc diffusion, MIC, and mecA gene detection respectively. Hospital acquired-MRSA strains were multi drug resistant while community acquired-MRSA showed susceptibility to clindamycin (63%), ciprofloxacin (24.2%) and SMZ/TMP (3.9%). In diagnosing MRSA, the sensitivity and specificity rates of disc diffusion test were 100% and 83.7% while MIC 96.2% and 93.3% respectively. Conclusion: There is an increasing trend in emergence MRSA and the conventional method of antimicrobial susceptibility testing showed false positive tests. This is the reason of misuse of vancomycin by physicians which may further increase MRSA in Pakistan. Therefore, molecular diagnostic facilities are recommended to avoid falsesusceptibleresults. Keywords: S. aureus, MRSA, mecA gene, MIC